A Note on a Class of Strongly Coupled Semilinear Reaction-diffusion Equations (Journal of Partial Differential Equations, 1995)
A class of strongly coupled semilinear reaction-diffusion equations is discussed. The FitzHugh-Nagumo equation in [1] is only an example. The results that strongly coupled term generates an analytic semigroup extended the results in [4]. The results of the existence and uniqueness of solution and the stability of zero solution improved that in [1]. This paper also discusses the existence of periodic solution.
Keywords: Strongly coupled; semilinear; semigroup